A Collections Planning Model for Regional Blood Suppliers: Description and Validation - Cumming, P. D.; Kendall, K. E.; Pegels, C. C.; Seagle, J. P.; Shubsda, J. F. (Management Science, 1976)
A planning model has been developed to assist regional blood suppliers in alleviating seasonal imbalances between supply and demand of blood. A Markovian population model is used to project various performance measures for a blood supply region. These measures are summarized in graphs covering a planning period of several months to one year. The planner improves projected performance by changing collection plans and using the planning model iteratively to evaluate each plan. The data required by the model are generally available: past performance of bloodmobile sponsors, quotas and demand forecasts. In this paper the model is described, projected performance measures are validated against actual measures, sensitivity to errors in inputs is analyzed and the model is evaluated relative to less complex models. The planning model is shown to be sufficiently accurate for its purpose and highly effective for its cost. It has been implemented by two regional blood suppliers using remote computer terminals.